Student’s Critical Thinking Ability In Ethnoscience-Based Biology Learning In The Era Of Digitalization - Muh Ilham; Sri Wahyuni; Muliana Muliana (Universitas Negeri Semarang, 2023)
This research aims to analyze the critical thinking abilities of MAN 1 Bone students in ethnoscience-based biology learning in the era of digitalization. This type of research is descriptive qualitative. The data processed are the results of student's critical thinking ability tests, observations and interviews with biology subject teachers and students with the highest test scores, three representatives from each class X.1, X.2 and X.5. The research results showed that student's critical thinking abilities based on the results of critical thinking ability tests in ethnoscience-based biology learning with ecosystem subjects for the even semester of the 2022-2023 academic year were in a very low category. Meanwhile, from learning activities, student's abilities are at varying levels based on critical thinking indicators. The indicator of providing further statements or explanations is at a fairly good level for the results of critical thinking ability tests and student learning activities. The indicators of providing basic statements or explanations, providing reasons for a decision, drawing conclusions or inferences, and providing feedback & reinforcement are at a level that is not good for critical thinking ability tests, while student learning activities are at a fairly good level. The results of this study indicate that it is important to increase student's mastery and understanding by integrating ethnoscience in learning so that they have critical thinking skills amidst the trend in the use of information technology.